An investigation into the relationship between climate change anxiety and mental health among Gen Z Filipinos - Reyes, Marc Eric S.; Carmen, Bianca Patricia B.; Luminarias, Moses Emmanuel P.; Mangulabnan, Soleil Anne Nichole B.; Ogunbode, Charles A. (Current psychology (New Brunswick, N.J.), 2023)
Climate change and mental health concerns are both defining issues of the generation of today. It has been established that the worsening climate causes many environmental disasters and physical health problems. However, its psychological impacts are still not well understood. Climate change has brought about an emerging psychological phenomenon termed ‘climate anxiety’ or ‘eco-anxiety,’ which has been described as a "chronic fear of environmental doom" (Clayton et al., 2017 , p. 68) due to the impact of climate change. This predictive cross-sectional study investigated the link between climate change anxiety and mental health among 433 Filipinos. A total of 145 males and 288 females aged 18 to 26 completed the Climate Change Anxiety Scale and the Mental Health Inventory (MHI-38). Results show a significant relationship between climate change anxiety and mental health, with climate change anxiety predicting 13.5% of the overall Mental Health Index variance. Significantly, climate change anxiety was associated with the MHI-38’s global scale of Psychological Distress but not with the global scale of Psychological Well-being. The findings are discussed concerning the broader context of research on the mental health impacts of climate change.